Hierarchical porous silicon structures with extraordinary mechanical strength as high-performance lithium-ion battery anodes - Jia, Haiping; Li, Xiaolin; Song, Junhua; Zhang, Xin; Luo, Langli; He, Yang; Li, Binsong; Cai, Yun; Hu, Shenyang; Xiao, Xingcheng; Wang, Chongmin; Rosso, Kevin M.; et al. (Nature communications, 2020)
Porous structured silicon has been regarded as a promising candidate to overcome pulverization of silicon-based anodes. However, poor mechanical strength of these porous particles has limited their volumetric energy density towards practical applications. Here we design and synthesize hierarchical carbon-nanotube@silicon@carbon microspheres with both high porosity and extraordinary mechanical strength (>200 MPa) and a low apparent particle expansion of ~40% upon full lithiation. The composite electrodes of carbon-nanotube@silicon@carbon-graphite with a practical loading (3 mAh cm −2 ) deliver ~750 mAh g −1 specific capacity, <20% initial swelling at 100% state-of-charge, and ~92% capacity retention over 500 cycles. Calendered electrodes achieve ~980 mAh cm −3 volumetric capacity density and <50% end-of-life swell after 120 cycles. Full cells with LiNi 1/3 Mn 1/3 Co 1/3 O 2 cathodes demonstrate >92% capacity retention over 500 cycles. This work is a leap in silicon anode development and provides insights into the design of electrode materials for other batteries. The authors here construct hierarchical porous CNT@Si@C microspheres as anodes for Li-ion batteries, enabling both high electrochemical performance and excellent mechanical strength. The work highlights the importance of mechanical properties in developing battery materials for practical applications.